Representation of Female Sexuality in Women's Narratives on "Creatalks Entertainment" Youtube Channel. - Asyiva, Ainilya Salwa; Kinanti, Aliyah Dewi; Rofinus, Christine Ananda Donna; Nurhadi, Muizzu (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2025)
This study explores the representation of female sexuality in women’s spoken narratives featured on the Creatalks Entertainment YouTube channel. The research focuses on three of the most viewd videos, each presenting a woman’s personal experience involving sex, power, and emotional complexity. Using Sara Mills’ feminist stylistics as a theoretical framework, the study analyzes how the women position themselves in their stories whether as agents, victims, or both. A descriptive qualitative approach was employed, with the primary data consisting of video transcripts. Rather than focusing on technical linguistic elements, the analysis examines the framing of sexuality through storytelling, emotional tone, and the social context of each experience. The findings reveal that while one woman portrays herself as a clear agent of her sexuality, the other two narrate experiences that reflect a blend of agency and victimhood shaped by manipulation, emotional debt, and power imbalance. These narratives illustrate the complexity of female sexuality when shaped by authority, trust, and cultural silence. This study highlights the importance of digital storytelling in revealing how women make sense of their sexual experiences within a patriarchal context. Keywords : Female Sexuality, Women”s Narratives, Creatalks Entertainment